Optimal transmission switching for power system integrating renewable energy based on analytical target cascading - Li, Rong; Ye, Pingfeng; Jiang, Donghai; Ma, Liwei; Sun, Chenhao (Frontiers in Energy Research, 2023)
The penetration rate of intermittent renewable energy in power system is gradually increasing, which brings challenges to the optimal dispatch of power system. In addition, the structure of the power system is becoming increasingly complex, showing a high degree of coupling and nonlinear characteristics, and the ordinary solution method can not meet the actual optimization needs. To solve these problems, a multi-regional interconnected transmission network optimization method based on analytical target cascading is proposed. Firstly, the reactive power regulation characteristics of renewable energy is investigated, and the models of wind turbine and photovoltaic generation are established. Secondly, the power system is decomposed into multiple sub-systems using bus tearing method, and an optimal transmission switching (OTS) model with renewable energies is established. Then, the analytical target cascading (ATC) approach is employed to decompose the model into the main problem and several sub-problems for parallel computation to achieve coordinated optimization of the complex transmission network. Finally, the IEEE 14-bus system and the IEEE 118-bus system are used to verify the proposed model.